Strategi Pengelolaan Zakat Profesi Sebagai Upaya Peningkatan Kesadaran Berzakat Pada Baznas Kota Palembang - Alvind Dwi Putra; Lemiyana; Chici Rima Putri Pratama (Jurnal Kajian Islam dan Sosial Keagamaan, 2024)
This research is entitled "Professional Zakat Management Strategy as an Effort to Increase Zakat Awareness at BAZNAS Palembang City." Zakat is an amount of property that must be spent by a Muslim who has fulfilled the terms and conditions of the Shari'ah with the aim of giving it to groups who in accordance with the Shari'a are entitled to receive zakat. The purpose of this research is to find out the strategies used by BAZNAS (Badan Amil Zakat) to increase awareness of zakat at BAZNAS, to find out the impact BAZNAS faces in managing professional zakat, and also to find out the solutions used by BAZNAS in dealing with obstacles in management. professional charity. This type of research is field research using a qualitative approach and descriptive research methods. The data collection tools used were observation, interviews and documentation methods. The data analysis techniques used are data reduction, data presentation and drawing conclusions. The results of the research show that the strategy used by BAZNAS is to use management functions such as planning, organizing, implementing, supervising, the aim is for people to believe that the zakat they give to BAZNAS in the city of Palembang is really well managed and given to people who need help and also so that people have the awareness to pay zakat. The impact faced by BAZNAS in managing professional zakat is the lack of awareness of muzakki to pay zakat at BAZNAS which is caused by several factors such as lack of public knowledge, people's mindset that is not yet open, and the community environment. The solution used by BAZNAS to face these obstacles is by holding outreach and education to increase public knowledge about professional zakat.